2023
DOI: 10.3390/biom13040705
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Tian et al. The Underlying Role of the Glymphatic System and Meningeal Lymphatic Vessels in Cerebral Small Vessel Disease. Biomolecules 2022, 12, 748

Abstract: In the published publication [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Such impairment impedes the clearance of neurotoxic substances. 31 Subsequently, neuroinflammation, myelin damage, and neurodegeneration occur, leading to clinical symptoms. The evolution of these pathological processes may go through a decade-long subclinical phase before clinical symptoms arise.…”
Section: Vascular Etiologies and Pathophysiology Of Vci Ischemic And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such impairment impedes the clearance of neurotoxic substances. 31 Subsequently, neuroinflammation, myelin damage, and neurodegeneration occur, leading to clinical symptoms. The evolution of these pathological processes may go through a decade-long subclinical phase before clinical symptoms arise.…”
Section: Vascular Etiologies and Pathophysiology Of Vci Ischemic And ...mentioning
confidence: 99%
“…Compromised neurovascular units, BBB integrity, and glymphatic system are causative in triggering amyloid/tau accumulation (eg, increased production and reduced clearance of amyloid) and the subsequent pathological cascades of AD. 31,[35][36][37] This causative role of cSVD is not only evident in the early development of late-onset AD but also in familial young onset autosomal dominant AD and in APOE ε4 carriers. 38,39 Clinical observational study using amyloid PET imaging showed that the number of midlife vascular risk factors (eg, hypertension, diabetes, hypercholesterolemia, obesity, smoking) was associated with increased amyloid deposition.…”
Section: Vascular Etiologies and Pathophysiology Of Vci Ischemic And ...mentioning
confidence: 99%